ANALYTICAL COMPARISON BETWEEN MASSIVE WOOD AND GLUED LAMINATED TIMBER IN CONSTRUCTION ELEMENTS - Mideva-Dimitrova, Milena; Roshavelov, Teodor (Innovation in Woodworking Industry and Engineering design, 2014)
The paper illustrates the potential for application of constructive-building components made of glued laminated timber, as alternative to traditionally used elements of solid wood. An example is proposed to demonstrate the promise of these structures by the use of finite element method. The comparison of the stress - strain state between structural element of solid wood and glulam is described in the paper, based on calculations, made according to the national regulations.Results and the comparison between them gives hope to expand the opportunities for effective application of glued laminated timber structures in the Bulgarian construction practice, as well as, for engineers, designers and architects, and with more complicated shapes and longer supporting distances.